The Interplay of Social, Emotional and Cognitive Factors of Risk Perception and Engagement in Precautionary Behaviors during COVID-19 Lockdown (4.0) in India - Kirti Tyagi (Intelektual Pustaka Media Utama, 2022)
To handle the pandemic of COVID-19, global health authorities are trying to identify factors that influence people’s behavioral patterns to engage in preventive measures. The present study examines the predictors of precautionary behaviors by adopting a socio-emotional-cognitive model of risk perception and provides a descriptive picture of people’s risk perception and precautionary behaviors during COVID19 lockdown in India. This was a cross-sectional online survey study, where data was collected from 203 participants in the age group of 18-67 years from different covid active zones of India using convenient sampling. The descriptive findings indicated that Indians displayed high participation in various precautionary behaviors (e.g., social distancing, washing hands, others) high level of awareness about the disease’s spread and symptoms, and high-risk perception (e.g., high perceived psychological vulnerability, disease severity, & personal impact). The participants also displayed a moderate to high level of worry towards the pandemic, with a moderate level of trust in the government’s ability to fight the pandemic. On the other hand, a significant positive relationship was observed between risk severity, perceived personal risk impact (cognitive factor) and level of anxiety towards pandemic (affective factor) and between the level of awareness (cognitive factor) and engagement in precautionary behaviors. However, only cognitive factors of risk perception (e.g., perceived psychological invulnerability & awareness about the diseases) were found out to be significant predictors for engagement in precautionary behaviors. Therefore, the present study emphasizes how health agencies should focus on creating risk messages that increase people’s estimation of personal risk and awareness towards the virus in order to raise community’s engagement in precautionary behaviors. Keywords: Risk Perception, Precautionary Behaviors, COVID19